Strengthening the self-esteem as a central concept of human development cross-cutting in children’s of transition a, Educational Institution Sofía Hernández Marín of Pereira (2019)
This article pretends to make known from a descriptive way how the self-esteem strengthen the human development of the transition children. The sample were the 12 transition A graders between 5 and 6 years from the educational institution Sofía Hernandez Marín from Pereira city and they correspond to a level 1 and 2 of social stratum population that have a big socioeconomic problem, the consequences that involve this children’s group which for this research was qualified as low self-esteem. The research instruments applied were observation, family drawing and the life history of each student. Done the study, children who have family support and assistance with family-teacher commitment, make better progress in their overall development, especially by encouraging self-esteem. Allowing this kids to have autonomy, resilience, ability to express their feelings and make a conscious position on situations that put them at risk vulnerability, harassment or abuse. Also helps to be supportive, cooperative, and sensitive; develop creativity, self-respectful and feel proud of themselves; also, walk towards realistic goals and, above all, transcend the different contexts in which they are and allow them to be happy. On the other hand, caregivers without interest, absent or indifferent families who don’t accompany their children, which has a negative impact on the formation of the children, that in this age live a big stage for their integral education. Esta situación requiere de mayor interés y acompañamiento desde la escuela, en cuanto al proceso de formación integral, en la relación docente-estudiante-familia, y sobre todo, en el seguimiento y acompañamiento al estudiante y su familia.